Decreased Interleukin‐20 Expression in Scleroderma Skin Contributes to Cutaneous Fibrosis - Kudo, Hideo; Jinnin, Masatoshi; Asano, Yoshihide; Trojanowska, Maria; Nakayama, Wakana; Inoue, Kuniko; Honda, Noritoshi; Kajihara, Ikko; Makino, Katsunari; Fukushima, Satoshi; Ihn, Hironobu (Arthritis & rheumatology (Hoboken, N.J.), 2014)
Objective To clarify the role of interleukin‐20 (IL‐20) in the regulatory mechanism of extracellular matrix expression and to determine the contribution of IL‐20 to the phenotype of systemic sclerosis (SSc). Methods Protein and messenger RNA (mRNA) levels of collagen, Fli‐1, IL‐20, and IL‐20 receptor (IL‐20R) were analyzed using polymerase chain reaction (PCR) array, immunoblotting, immunohistochemical staining, enzyme‐linked immunosorbent assay, and real‐time PCR. Results PCR array revealed that IL‐20 decreased gene expression of α2(I) collagen (0.03‐fold), Smad3 (0.02‐fold), and endoglin (0.05‐fold) in cultured normal dermal fibroblasts. Fli‐1 protein expression was induced by IL‐20 (∼2‐fold). The inhibition of collagen by IL‐20, the induction of Fli‐1 by IL‐20, and the reduction of Smad3 and endoglin by IL‐20 were also observed in SSc fibroblasts. Serum IL‐20 levels were reduced only slightly in SSc patients but were significantly decreased in patients with scleroderma spectrum disorders (the prodromal stage of SSc) compared with those in normal subjects (111.3 pg/ml versus 180.4 pg/ml; P < 0.05). On the other hand, IL‐20 mRNA expression in SSc skin was decreased compared with that in normal skin (P < 0.05), which may result in the induction of collagen synthesis in SSc dermal fibroblasts. IL‐20R was expressed in normal and SSc fibroblasts. Moreover, IL‐20 supplementation by injection into the skin reversed skin fibrosis induced by bleomycin in mice (∼0.5‐fold). Conclusion IL‐20 reduces basal collagen transcription via Fli‐1 induction, while down‐regulation of Smad3 and endoglin may cancel the effect of transforming growth factor β in SSc fibroblasts. To confirm the therapeutic value of IL‐20 and IL‐20R, their function and expression in vivo should be further studied.